Student Perception of Entrepreneurial Studies and Graduate Employment Prospect in the Polytechnic Ibadan - Ajani, Mary Oluwatoyin (International Journal of Educational Management, 2021)
This study investigated student perception of entrepreneurial studies as predictor of graduate employment prospect in the polytechnic Ibadan. It has been studied that there is a mismatch between skills and job opportunity in Nigerian education sector. The training which tertiary students receive has not been fully successful in equipping them with desirable skills and competencies required for job creation and self-employment. The study adopted descriptive survey research design of the ex-post facto type. The sample consisted of final year students at OND II and HND II students across the five faculties in the polytechnic Ibadan, Oyo state, Nigeria. Stratified random sampling techniques were used in selecting a total of five hundred and sixty (560) participants across the faculties in the Polytechnic Ibadan, Oyo state, Nigeria. A Questionnaire tagged “Student Perception of Entrepreneurial Studies” developed and used to collect data for the study. t-test and regression analysis were used to analyze the data collected. Significant gender different in career prospect among students (t(df=546)= 57.474, P<0.05). Male were not different from female on their perception of being employed after graduation (t (df=546) = .422, P>0.05). Joint influence of entrepreneurial skills acquired by the students contributed significantly to their entrepreneurial intention (R = .384; R = .147; F2= 2.830; p <.05). . (5 ,7) Findings further revealed that there is significant difference in the career prospects of students based on gender in the Polytechnic, Ibadan, Oyo state. Therefore, it was recommended that Rectors overseeing the affairs of the polytechnics should invest massively in training of specialists in the field of entrepreneurship educations. Experts with practical experience in entrepreneurship from the industry could also be engaged on full or part-time arrangement. It was also recommended that every polytechnic should evolve a culture of entrepreneurship by supporting, training and rewarding their self-reliant graduates.